2014
DOI: 10.1111/ics.12177
|View full text |Cite
|
Sign up to set email alerts
|

Cellulite: poor correlation between instrumental methods and photograph evaluation for severity classification

Abstract: Cellulite caused impact in quality of life. Poor correlation between objective measures and clinical evaluation was detected. Cellulite severity assessment is a challenge, and objective parameters should be optimized for clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
0
16
0
3
Order By: Relevance
“…Cellulite is a skin discomfort developed by multiple factors (8) but the main etiology is not completely understood (9). The appearance of skin changes and it becomes like an “orange peel”.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellulite is a skin discomfort developed by multiple factors (8) but the main etiology is not completely understood (9). The appearance of skin changes and it becomes like an “orange peel”.…”
Section: Contextmentioning
confidence: 99%
“…The Nurnberger and Muller scale is the most commonly used classification for cellulite (9, 13). According to this scale, three grades were defined: I- visible changes with skin clamping or muscle contraction; II- visible changes without manipulation; and III- visible changes associated with nodules.…”
Section: Contextmentioning
confidence: 99%
“…Their clinical relevance remains arguable. Although photonumeric cellulite grading (5-point scale) and BMI were positively correlated with severity scores (10-point scale) in a study by Soares et al,28 high-frequency (20 MHz) ultrasound results and skin elasticity scores were not. A study by Smalls et al29 also showed that biomechanical properties were not correlated with cellulite severity, but BMI and architecture of the dermal–subcutaneous junction were.…”
Section: Clinical Features and Severity Gradingmentioning
confidence: 82%
“…It has been classified as one of the worst-tolerated symptoms by women [6]. As such, it attracted numerous studies related to pathophysiology [7,8] diagnosis [6,9,10] prevention and treatment through various anti-cellulite therapies [11][12][13][14]. Cellulite-specific symptoms appear as uneven, wrinkled skin surface with numerous thickenings, bulges and furrows, which represent defects and a weakening of connective tissues.…”
Section: Introductionmentioning
confidence: 99%